Development of A Healthy Madrasah Service Management Model (Research At Man 2 Bandung City and MAN Kab 1 Sumedang) - Nurasa, Ace; Priatna, Tedi; Jahari, Jaja; Samsul Arifin, Bambang (Sahabat Publikasi, 2024)
Islam is a religion that embraces all aspects of life with complete attention, not only those related to rituals and ideological concepts but also holistically. In Islam, cleanliness and purity are both equally important, because cleanliness alone is not enough to be able to face God or worship. Until now, there are still many schools/madrasas in Indonesia that have poor sanitation quality. A healthy and conducive school environment is very much needed to create a quality learning process. The purpose of this study is to create an effective healthy madrasa service management model in the future. Curriculum related to the environment, for example, can be implemented in various ways. First, environmental education is included in the school curriculum. The syllabus and lesson plan (RPP) are examples of learning planning, and the role of teachers is very important in instilling environmental awareness. Second, the principle of character is included in extracurricular activities, such as scouts. Extracurricular activities such as scouts have a direct relationship with nature. Third, participate in activities related to the environment. The approach in this study is a qualitative approach. Qualitative research with descriptive research methods that aim to create descriptions, create pictures, paintings systematically, factually and accurately regarding data, characteristics and relationships of the phenomena studied. Data collection techniques in research: Open, structured interviews, or a combination thereof, Closed, open questionnaires, or a combination thereof. The findings obtained in this study are that a healthy and conducive school environment is very necessary in order to create a quality learning process. Providing knowledge and forming awareness about clean and healthy living behavior in the school environment will be more effective when carried out on students since they are in Madrasah Aliyah, so that it becomes a habit from an early age. By being instilled since in Islamic schools, it is also expected to become a habit when outside the school environment. The healthy madrasah program is often hampered by inadequate facilities and infrastructure, such as inadequate sanitation, dirty canteens and a culture of clean living that has not been implemented. From the results of the evaluation and observation in the madrasah, there are indications of various conditions such as the lack of attention to facilities/infrastructure, knowledge, attitudes of students in the field of health, madrasah canteens, food, personal health.